Inflammation and depression: combined use of selective serotonin reuptake inhibitors and NSAIDs or paracetamol and psychiatric outcomes. Issue 8 (29th May 2015) - Köhler, Ole; Petersen, Liselotte; Mors, Ole; Gasse, Christiane
Abstract Background Nonsteroidal anti‐inflammatory drugs (NSAIDs) and paracetamol have been shown to yield the potential of adjunctive antidepressant treatment effects to selective serotonin reuptake inhibitors (SSRIs); however, when investigating treatment effects of concomitant use, simultaneous evaluation of potential adverse events is important. The objective was thus to investigate treatment effectiveness and safety aspects of concomitant SSRI use with NSAIDs or paracetamol. Methods Within a 25% random sample of the Danish population, we identified all incident SSRI users between 1997 and 2006 (N = 123, 351). Effectiveness and safety measures were compared between periods of SSRI use only and periods of combined SSRI and NSAID or paracetamol use by applying Cox regression. Results Among 123, 351 SSRI users (follow‐up: 53, 697.8 person‐years), 21, 666 (17.5%) used NSAIDs and 10, 232 (8.3%) paracetamol concomitantly. Concomitant NSAID use increased the risk of any psychiatric contact [Hazard rate ratio (95%‐confidence interval): 1.22 (1.07; 1.38)] and with depression [1.31 (1.11; 1.55)]. Low‐dose acetylsalicylic acid reduced the risk of psychiatric contact in general [0.74 (0.56; 0.98)] and with depression [0.71 (0.50; 1.01)]. Ibuprofen reduced the risk of psychiatric contacts [0.76 (0.60; 0.98)]. Concerning safety, paracetamol was associated with increased mortality [3.18 (2.83; 3.58)], especially cardiovascular [2.51 (1.93; 3.28)]. Diclofenac [1.77 (1.22; 2.55)] and the selective COX‐2 inhibitors [1.75 (1.21; 2.53)] increased mortality risks. Conclusions Concomitant use of SSRIs and NSAIDs occurred frequently, and effectiveness and safety outcomes varied across individual NSAIDs. Especially low‐dose acetylsalicylic acid may represent an adjunctive antidepressant treatment option. The increased mortality risk of concomitant use of paracetamol needs further investigation.